Gorgias’ Argument does not Include Actual Conditionals - López - Astorga, Miguel (Problemos, 2018)
[straipsnis ir santrauka anglų kalba, santrauka lietuvių kalba]It can be thought that Gorgias’ argument on the non-existence consists of three sentences, the first one being an asseveration and the other two being conditionals. However, this paper is intended to show that there is no conditional in the argument, and that the second and third sentences only appear to be so. To do that, a methodology drawn from the framework of the mental models theory is used, which seems to lead to the true logical forms of these last sentences as well.
Keywords: conditional, Gorgias, logical form, mental models theory, non-existence